Efektivitas Latihan Rentang Gerak dalam Meningkatkan Kekuatan Otot pada Lansia dengan Gangguan Mobilitas Fisik di BPSTW Budi Luhur DIY - Ayu Manila, Larasia Gloria; Riyadi, Sujono; Prayitno , Sidik (Jurnal Indonesia Sehat, 2024)
Background: Stroke is a disease caused by a failure in the blood supply to the brain that occurs over 24 hours and can result in death. The priority nursing problem in the elderly with stroke is impaired physical mobility or hemiparesis of the limbs. Purpose: the author's aim is to see the effectiveness of range of motion (ROM) exercise to increase post-stroke muscle strength at BPSTW Budi Luhur DIY Social Service. Method: the research method is a case study. The case study subject used one patient who experienced limb weakness and post-strok with impaired physical. mobility. Researchers conducted a nursing care process from assessment to evaluation for 3 days. Results: the results showed that the patient complained of weakness in the left upper and lower extremities. The patient has had a stroke since 5 years ago and bedrest until now, a muscle strength examination was obtained, left upper and lower extremity muscle strength 1 and 0. Conclusion: based on the data obtained, the patient had impaired physical mobility. Researchesrs provided ROM intervention for three days. The action of ROM for 3 days showed a change in the patient's uscle strength value, so it can be concluded that ROM is effectively given to help increase the muscle strength of patients who experience weakness.